THE EFFECT OF D-WALL EMBEDMENT MODELLING ON THE SEISMIC RESPONSE OF UNDERGROUND STRUCTURES AT MRT STATIONS IN JAKARTA - Dwi Lestari Salamah, Mirna
Efficient and sustainable urban transportation systems are key elements in the development of major cities worldwide. The demand for reliable public transportation systems, such as subways or MRT, is increasing alongside the rising urbanization. Although underground structures are considered safe due to the natural support provided by the soil, the importance of seismic analysis cannot be overlooked given the risk of earthquake damage, particularly in vulnerable regions like Indonesia. In practical design applications, seismic analysis of underground structures often employs simplified framework approaches, which assume conservative structural geometry without modeling the length of D-wall penetration. However, this research reveals inconsistent trends, with some studies showing a significant increase in the racking ratio of underground station models with D-wall, while others indicate smaller deformations in structures with D-wall. Therefore, this study aims to clarify the impact of D-wall on seismic behavior through parametric analysis of 48 models considering various variables, including earthquake intensity, site class, structural geometry, and D-wall penetration length. The research utilizes finite element methods, examining both dynamic and pseudo-static analysis. The results show that the effect of D-wall modeling is practically insignificant with the difference in deformation shown rangingfrom 0.057-1.49 mm. In terms of internal force, the model without D-wall has a larger dynamic bending moment increase of about 14-25% compared to the model with D-wall legs. The difference in research results with previous research is due to the different D-wall models used. Some previous studies assumed that the D-wall is separated from the shear wall of the structure itself so that it can increase stiffness and reduce the amount of deformation that occurs.